Answer:
150 cm
Explanation:
The information in the question includes;
The length of rope P = 3 × The length of rope Q
The length of rope P - 10 cm = 4 × (The length of rope Q - 10 cm)
Let p represent the original length of rope P and let q represent the original length of rope Q, we have;
p = 3·q...(1)
p - 10 = 4·(q - 10)...(2)
Expanding equation (2) gives;
p - 10 = 4·q - 40
∴ p = 4·q - 40 + 10 = 4·q - 50
p = 4·q - 50...(3)
Equating the values of p in equation (1) and equation (3) gives;
p = 3·q, and p = 4·q - 50, therefore, by the substitution property of equality, we have;
3·q = 4·q - 50
50 = 4·q - 3·q = q
q = 50
p = 3·q
∴ p = 3 × 50 = 150
The original length of P before it was cut, p = 150 cm.